The Implementation Of State Responsibility Principle in Indonesia Concerning Plastic Waste of Pacific Ocean - Zulkhanadya Zulkhanadya; Sophia Listriani (Syiah Kuala Law Journal, 2020)
Today, plastic waste is the most widely found in the Pacific Ocean, around 99% of garbage in the Pacific Ocean is plastic waste. Indonesia as the second-largest contributor plastic waste to sea, it needs to implement the state responsibility principle to fulfill the international obligations as referred to article 235 (1) of the United Nations Convention on the Law of the Sea (UNCLOS) 1982, stated that states are responsible for the fulfillment of their international obligations concerning the protection and preservation the marine environment. The state responsibility principle is also discussed at the national level, in Indonesia itself, there is a national regulation that discusses the state responsibility principle such as Law No. 32 of 2009 on environmental protection and management. Therefore, this paper will discuss the implementation of state responsibility principle in Indonesia and the challenges faced by Indonesia in implementing the state responsibility principle.